REPELLENT ABILITY OF LERAK (Sapindus rarak DC) FRUIT EXTRACT AND KIRINYUH (Chromolaena odorata L.) LEAF EXTRACT ON Callosobruchus maculatus F WAREHOUSE PESTS - Suryaningsih, Siti; Rochman, Nur; Adi, Setyono (Universitas Djuanda Bogor, 2017)
The aim of this research is to know the repellent ability of lerak fruit extract (Sapindus rarak DC.) and kirinyuh leaf extract (Chromolaena odorata) against Callosobruchus maculatus warehouse pests. The research activity was conducted in October - December 2016 at Entomology Laboratory, SEAMEO BIOTROP Bogor. This research used two experiments that were using lerak fruit extract and kirinyuh leaf extract. The experimental design used was Completely Randomized Design with three replications for each concentration level of extract material. The extract concentrations used for the preliminary test were 1.0%; 2.0%; 3.0%; 4.0% and 5.0%. In the main test the concentration refers to the results of the preliminary test. The concentration of lerak fruitÂ extract used for the main test were 1.5%; 3.0%; 4.5%; 6.0% and 7.5% (v / v), the concentration of kirinyuh leaf extract were 0.0%; 2.5%; 5.0%; 7.5% and 10.0% (v / v). The effectiveness of repellent ability be classified well if repellent â¥80%, good enough if 60% â¤ repellent <80% and less good if repellent <60%. The highest repellent content of lerak fruit extract on 72Â hours after treatment (JSP) was 77.9% occurring at 4.5% extract concentration and highest repellent of kirinyuh leaf extract on 72 JSP was 82.73% occurring at 10.0% extract concentration. Repellent ability of kirinyuh leaf extract is better than repellent ability of lerak fruit extract. Keywords: repellent power, vegetable extract, extract concentration, pest controlling